Discovery and development of surotomycin for the treatment of Clostridium difficile. (1st March 2016) - Knight-Connoni, Victoria; Mascio, Carmela; Chesnel, Laurent; Silverman, Jared
Abstract: The primary challenge for treating Clostridium difficile infections (CDI) is maintenance of clinical response after the end of treatment (sustained clinical response). Disease recurrence following a positive clinical response occurs in approximately 6–25 % of patients after the first episode and in up to 65 % for subsequent recurrences. Surotomycin, a novel cyclic lipopeptide antibiotic with a core derived by Streptomyces roseosporus fermentation, disrupts C. difficile cellular membrane activity in both logarithmic and stationary phases and minimally disturbs normal gastrointestinal microbiota because of its lack of activity against Gram-negative anaerobes and facultative anaerobes. Preclinical and clinical evidence indicate that surotomycin has low oral bioavailability, allowing gastrointestinal tract concentrations to greatly exceed its minimum inhibitory concentration for C. difficile . Surotomycin is well tolerated and effective in hamster models of CDI. Phase 2 clinical evidence suggests that surotomycin (250 mg twice daily) is an effective CDI treatment, with statistically lower recurrence rates than vancomycin.